US independent film after 1989 : possible films - Perkins, Claire (Claire Elizabeth); Verevis, Constantine (Edinburgh University Press, 2015)
A study of US independent films marginalized in and by the rise of 'indie' culture. In contemporary film and popular culture the terms 'independent' and 'indie' hold instant recognition and considerable cultural cachet. As both a brand of American filmmaking and a keynote of critical film discourse, indie denotes specific textual, industrial and reception practices that have been enthusiastically cultivated across the last decade of the twentieth century and the first of the twenty-first. Underpinning this cultural category is a canon of highly visible films and filmmakers whose 'maverick' personas and self-aware stylisation have successfully sold indie as a quality, alternative worldview-figures like Quentin Tarantino, Joel and Ethan Coen, Kevin Smith and Wes Anderson, and films like Slacker, Memento, Happiness and Juno. US Independent Film After 1989: Possible Films reframes this dominant indie canon by attending to a group of films that have not been so fully subsumed by its critical and promotional rhetoric. In 20 close analyses, a diverse range of leading film scholars and commentators allow the contours of the indie sensibility to emerge in and through their individual experiences of a single film that has not received the sustained critical acclaim of more popular titles. With particular representation from female directors-who are almost wholly excluded from the dominant indie canon-these idiosyncratic films are shown to demonstrate central tenets of indie scholarship and simultaneously emphasise the classifying processes that obscure them. Key Features: Provides 20 textual studies of under-evaluated US indie film Develops an expanded understanding of US indie film culture Identifies the contribution of a community of US indie filmmakers and actors, with a particular emphasis on women practitioners